Targeted Next-Generation Sequencing of Circulating Tumor DNA, Bone Marrow, and Peripheral Blood Mononuclear Cells in Pediatric AML - Ruan, Min; Liu, Lipeng; Qi, Benquan; Chen, Xiaoyan; Chang, Lixian; Zhang, Aoli; Liu, Fang; Wang, Shuchun; Liu, Xiaoming; Chen, Xiaojuan; Zhang, Li; Guo, Ye; et al. (Frontiers in Oncology, 2021)
Background The aim of the study was to validate the diagnostic role of circulating tumor DNA (ctDNA) in genetics aberration on basis of next-generation sequencing (NGS) in pediatric acute myeloid leukemia (AML). Methods Bone marrow (BM) and peripheral blood (PB) were collected from 20 AML children at the time of initial diagnosis, and ctDNA sample was isolated from PB. Detection of mutation was performed on ctDNA, BM and peripheral blood mononuclear cell (PBMC) by NGS based on a 185-gene panel. Results Among 185 genes sequenced by NGS platform, a total of 82 abnormal genes were identified in 20 patients. Among them, 61 genes (74.39%) were detected in ctDNA, PBMC and BM samples, while 11 (13.41%) genes were found only in ctDNA and 4 (4.88%) were detected only in BM sample, 2 (2.44%) were detected only in PBMC. A total of 239 mutations were detected in three samples, while 209 in ctDNA, 180 in bone marrow and 184 in PBMC. One hundred and sixty-four mutations in ctDNA were shared by matched BM samples, and the median variant allelic frequency (VAF) of these mutations was 41.34% (range, 0.55% to 99.96%) and 44.36% (range, 0.56% to 99.98%) in bone marrow and ctDNA. It was found that 65.79% (75/114) of mutations with clinical significance were detected in three samples, with 9 mutations detected both in ctDNA and BM, and 2 mutations detected both in PBMC and BM. The consistency of mutations with clinical significance between ctDNA and BM was 77.06% (84/109). Among the 84 mutations with clinical significance detected in both sources, the concordance of VAF assessment by both methods was high (R2=0.895). Conclusion This study demonstrates that ctDNA was a reliable sample in pediatric AML and can be used for mutation detection. Consistency analysis showed that ctDNA can mirror the genomic information from BM. In addition, a subset of mutations was exclusively detected in ctDNA. These data support that monitoring ctDNA with next-generation sequencing-based assays can provide more information about gene mutations to guide precision treatment in pediatric AML.